“Control biológico de stemphyllium solani utilizando biotipos de trichoderma en el cultivo de tomate (lycopersicum esculentum L.), en sector aucaloma-San Martín -Perú” - Reátegui Paima, Manolo (2015)
The research with the aim of isolating biotypes of Trichoderma sp from different places and assess the impact of biological control using Trichoderma sp Stemphyllium solani causing "tomato blight or gray leaf spot" in San Martin. The experiment in running Plant Health Laboratory-Pathology, located in University City in the district of Morales and the Fundo Aucaloma located to 15 km from the district of Morales, South Latitude 6 º 20 'West Longitude 76 º 21' 720 m.s.n.m.m altitude area of tropical moist forest life (bh-PT) within the jurisdiction of the district San Antonio Rio Cumbaza, province and region of San Martin. Both are from the National University of San Martin - Tarapoto; under completely randomized block design with tour replications and eight treatments. Were isolated and multiplied, six strains of Trichoderma sp. They were coded as CFC (founded Cepa cacatache) CJG (Cepa Juan Guerra), CSP (Cepa Sector palms), CTO (Cepa October 3), CMO (Cepa Morales) CMA (Cepa Morales isolated from rice plant). six strains of Trichoderma sp, applied in tomato plants, have shown the best biocontrol of tomato leaf blight caused by the fungus Stemphylium solani that decreased the incidence and severity of disease, the strains CJG 34.45% and 17.76% of AFA, CMO with 30.55% and 15.74% of AFA and CTO strain with 38.03% and 19.6% of AFA. The six strains of Trichoderma sp, applied ata rate of 3 kg/ha, they have contributed to the growth and development of the tomato plant giving yields between 38 448.41 to 53 442.00 kg I ha. Keyword: Trichoderma biological control Stemphylium, leaf blight